APPLICATION OF INTUITIONISTIC FUZZY CRITICAL PATH MODEL FOR SELECTION OF BEST PERFORMER - T. S Viswanadham; B. Pardha Saradhi; G. Vasanti (Utilitas Mathematica, 2025)
The main objective of this article is to apply the intuitionistic fuzzy critical path model to identify the best performer in an institute/competition or a best performer during B.Tech course. The process of application of Intuitionistic Fuzzy Critical Path to identify the best performer at the completion of a course is explained in this article with an example using Trapezoidal intuitionistic fuzzy numbers. The criterion of selection is by defining the required characteristics, say the academic achievements, skills, leadership qualities, ethics/attitude, etc may include. The entire process of selection may be broken down into different small goals like achieving qualification, skill1, skill2, skill3, etc. Arrange the goals/skills/activities in an order to be acquired by the student and observing the time taken by the candidate to acquire each activity. Then the best performer can be estimated by using intuitionistic fuzzy critical path model.